PELATIHAN AKUNTANSI MENGENAI PENYUSUNAN LAPORAN KEUANGAN PERUSAHAAN JASA DENGAN METODE SPEENING WHEEL DI SMA SANTO KRISTOFORUS 1 - Widjaja, Karen; Suhendah, Rousilita (Jurnal Serina Abdimas, 2023)
ABSTRACT This accounting training activity aims to provide knowledge regarding the preparation of financial reports for service companies to students at SMA Santo Kristoforus 1 on Jl. Rahayu, West Jakarta. This accounting training activity is carried out offline or face to face so that Tarumanagara University students teach directly at Santo Kristoforus 1 High School. This accounting training uses the Speening Wheel method which is carried out by Tarumanagara University students for Santo Kristoforus 1 High School students. Material provided to students is a theory of preparing financial reports for service companies that is accompanied by practice questions and games that have been designed by Tarumanagara University students to help students understand the material that has been presented. By holding this training, it can be seen that students at Santo Kristoforus 1 High School understand the material that has been presented, as can be seen from the enthusiasm of the students in answering the questions given related to the material that has been presented and are able to solve the games or games given related to the material provided. After this training, it is hoped that students will be able to understand more about the preparation of financial reports for service companies and that the material presented will be useful for them in continuing their education at university. ABSTRAK Kegiatan pelatihan akuntansi ini bertujuan untuk memberikan ilmu pengetahuan mengenai penyusunan laporan keuangan perusahaan jasa kepada peserta didik SMA Santo Kristoforus 1 di Jl. Rahayu, Jakarta Barat. Kegiatan pelatihan akuntansi ini dilaksanakan secara offline atau tatap muka sehingga mahasiswa Universitas Tarumanagara mengajar langsung di sekolah SMA Santo Kristoforus 1. Pelatihan akuntansi ini menggunakan metode Speening Wheel yang dilaksanakan oleh mahasiswa Universitas Tarumanagara kepada peserta didik SMA Santo Kristoforus 1. Materi yang diberikan kepada peserta didik adalah teori penyusunan laporan keuangan perusahaan jasa yang disertakan dengan soal latihan dan permainan yang telah dirancang oleh mahasiswa Universitas Tarumanagara untuk membantu peserta didik dalam memahami materi yang telah disampaikan. Dengan diadakannya pelatihan ini dapat dilihat bahwa peserta didik SMA Santo Kristoforus 1 memahami materi yang telah disampaikan, terlihat dari antusiasme peserta didik dalam menjawab pertanyaan-pertanyaan yang diberikan terkait dengan materi yang telah disampaikan dan mampu menyelesaikan soal games atau permainan yang diberikan terkait dengan materi yang telah disampaikan. Setelah pelatihan ini diharapkan peserta didik dapat lebih memahami mengenai penyusunan laporan keuangan perusahaan jasa dan materi yang disampaikan dapat berguna untuk mereka dalam melanjutkan pendidikannya di perguruan tinggi.